Optimization of serum thyroglobulin measured at different time points for prognostic evaluation in differentiated thyroid carcinoma patients. Issue 14 (April 2020) - Mutsuddy, Pupree; Jeon, Subin; Yoo, Su Woong; Zhang, Yingjie; Chowdhury, Md. Sunny Anam; Kim, Jahae; Song, Ho-Chun; Bom, Hee-Seung; Min, Jung-Joon; Kwon, Seong Young
Abstract : Abstract: Although serum thyroglobulin (Tg) is a reliable differentiated thyroid carcinoma (DTC) prognostic marker, its cutoff values can be affected by TSH stimulation status. Serum Tg prognostic values measured at different time points before and after radioactive iodine (RAI) therapy prepared with recombinant human TSH (rhTSH) in DTC patients, were investigated. This study included 160 DTC patients who underwent surgery followed by rhTSH-aided RAI therapy. Their serum Tg levels were measured 7 days before (D-7Tg), on the day of (D0Tg), and 2 days after (D2Tg) the RAI therapy. For response evaluation, the patients were classified into 2 groups: acceptable response and non-acceptable response (non-AR). Optimal Tg level cutoff values measured at different time points were evaluated for persistent or recurrent disease (PRD) prediction, as well as therapeutic response. Multivariate analysis showed that D-7Tg, D0Tg, and D2Tg significantly predicted non-AR ( P < .05, for all). Optimal Tg level cutoff values for non-AR prediction were 0.6, 2.6, and 3.7 ng/mL for D-7Tg, D0Tg, and D2Tg, respectively. Cox regression analysis showed that Tg levels were significantly associated with PRD free survival with D-7Tg, D0Tg, and D2Tg cutoff values of 0.8, 4.0, and 6.0 ng/mL, respectively (D-7Tg, P = .010; D0Tg, P = .005; D2Tg, P = .011). Serum Tg levels measured at the different time points could predict PRD free survival as well as therapeutic response with different cutoff values in DTC patients who underwent rhTSH-aided RAI therapy.